2007
DOI: 10.1016/j.drugalcdep.2006.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Voucher reinforcement improves medication adherence in HIV-positive methadone patients: A randomized trial

Abstract: This clinical trial evaluated a contingency management intervention designed to improve medication adherence among HIV-positive methadone maintenance patients. After a 4-week baseline observation phase, eligible participants (N = 66) were randomly assigned to: (a) medication coaching sessions every other week to assist with adherence strategies (comparison group) or (b) medication coaching plus voucher reinforcement for opening electronic medication caps on time (voucher group). Baseline adherence (percent dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
136
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(137 citation statements)
references
References 42 publications
1
136
0
Order By: Relevance
“…This procedure, known as Bcontingency management^(CM), has been used to treat substance abuse [8], increase asthma and HIV medication adherence [9][10][11], increase physical activity levels and facilitate weight loss [12,13], and improve diabetes self-management in children and adolescents [14][15][16]. Contingency management has also been shown to be more effective when combined with other psychosocial interventions, such as motivational interviewing (MI) [17].…”
Section: Introductionmentioning
confidence: 99%
“…This procedure, known as Bcontingency management^(CM), has been used to treat substance abuse [8], increase asthma and HIV medication adherence [9][10][11], increase physical activity levels and facilitate weight loss [12,13], and improve diabetes self-management in children and adolescents [14][15][16]. Contingency management has also been shown to be more effective when combined with other psychosocial interventions, such as motivational interviewing (MI) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Some barriers to adherence for patients include limited access to facilities, costs associated with filling prescriptions or doctors visits, side effects of the treatment, drug and or alcohol abuse, and depression. Table 1 [16][17][18][19][20][21][22]), but more quantitative evidence (particularly in terms of improvement in virological or immunological outcomes) regarding effectiveness of different adherence promoting interventions is needed [23]. A meta-analysis of interventions to improve patient adherence to ART found that the interventions to improve poor adherence had greater effect size than studies recruiting patients with mixed adherence profiles [24].…”
Section: Treatment Adherencementioning
confidence: 99%
“…sustained-release, transdermal and sublingual film formulations) (Fudala & Johnson, 2006), prescription monitoring programs (Fishman, Papazian, Gonzalez, Riches, & Gilson, 2004;Pradel et al, 2009) and the use of RFID (radio frequency identification) technology or electronic adherence monitoring (Fudala & Johnson, 2006). So far, previous studies on electronic monitoring in OST have used it to obtain reliable and detailed adherence data (Arnsten et al, 2001;Fiellin et al, 2006;Sorensen et al, 2007). Our 4-week pilot study examining electronic compliance monitoring in 12 BNX treated OST patients indicated that monitoring was well accepted and subjectively increased compliance (Tacke, Uosukainen, Kananen, Kontra, & Pentikäinen, 2009).…”
Section: Introductionmentioning
confidence: 99%